2021
DOI: 10.1371/journal.pntd.0009191
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and clinical management of hepatosplenic schistosomiasis: A scoping review of the literature

Abstract: Background Hepatosplenic schistosomiasis (HSS) is a disease caused by chronic infection with Schistosma spp. parasites residing in the mesenteric plexus; portal hypertension causing gastrointestinal bleeding is the most dangerous complication of this condition. HSS requires complex clinical management, but no specific guidelines exist. We aimed to provide a comprehensive picture of consolidated findings and knowledge gaps on the diagnosis and treatment of HSS. Methodology/principal findings We reviewed relev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 98 publications
0
27
0
5
Order By: Relevance
“…Hepatosplenic schistosomiasis is a heterogeneous condition, ranging from a mildly symptomatic to life-threatening disease [ 45 ] ( Figure 4 ). The most common presentation of hepatosplenic schistosomiasis was upper gastrointestinal bleeding leading to severe anemia [ 46 ].…”
Section: Hepatosplenic Schistosomiasismentioning
confidence: 99%
See 1 more Smart Citation
“…Hepatosplenic schistosomiasis is a heterogeneous condition, ranging from a mildly symptomatic to life-threatening disease [ 45 ] ( Figure 4 ). The most common presentation of hepatosplenic schistosomiasis was upper gastrointestinal bleeding leading to severe anemia [ 46 ].…”
Section: Hepatosplenic Schistosomiasismentioning
confidence: 99%
“…The most common presentation of hepatosplenic schistosomiasis was upper gastrointestinal bleeding leading to severe anemia [ 46 ]. In contrast to cirrhosis, in hepatosplenic schistosomiasis, hepatic function is preserved overall [ 45 ]. Several studies have demonstrated a correlation between disease severity (measured by i.e., organomegaly) and quantitative fecal egg output [ 47 ].…”
Section: Hepatosplenic Schistosomiasismentioning
confidence: 99%
“…v) Splenic schistosomiasis, which may present as calcification, may occur following a history of contact with contaminated water. Further, it may present with symptoms such as anemia, leukopenia, thrombocytopenia, or hypersplenism ( 26 ). vi) Splenic hamartoma, which is rare and largely without obvious symptoms, may have cystic degeneration, calcification, and fat components.…”
Section: Discussionmentioning
confidence: 99%
“…Currently, surgical procedures are the best researched and most favored definitive therapy for HSS despite their high-grade invasiveness, perioperative mortality and the consequences of post-splenectomy syndrome. [14,15].…”
Section: Introductionmentioning
confidence: 99%